Green synthesis of silver nanoparticles using Cordia dichotoma fruit extract and its enhanced antibacterial, anti-biofilm and photo catalytic activity. (18th May 2018) - Bharathi, Devaraj; Vasantharaj, Seerangaraj; Bhuvaneshwari, V
Abstract: The present study describes the antibacterial, anti-biofilm and photo catalytic activity of silver nanoparticles synthesized using Cordia dichotoma fruits (Cd-AgNPs) for the first time. The phyto-synthesized Cd-AgNPs were characterized by UV-Visible spectroscopy, Field emission-scanning electron microscopy (FE-SEM), Transmission electron microscopy (TEM), Energy dispersive x-ray spectrometer (EDX), Fourier transform infrared spectroscopy (FT-IR), and x-ray diffraction (XRD). FE-SEM and TEM observation showed that the average size of 2–60 nm with spherical shape of Cd-AgNPs and the presence of phyto-compounds which are responsible for capping and reduction were studied by FT-IR. XRD studies revealed the face-centered cubic structure of Cd-AgNPs. The synthesized Cd-AgNPs showed significant antibacterial activity against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli, assayed using agar well diffusion method. Phyto-synthesized Cd-AgNPs exhibited more than 90% inhibition of biofilm activity formed by S. aureus and E. coli . Furthermore, photocatalytic degradation of crystal violet (CV) under UV light irradiation using Cd-AgNPs was performed. Synthesized Cd-AgNPs exhibited ∼85% degradation activity for CV. Collectively, our findings suggest that C.dichotoma is a green source for the eco-friendly synthesis of Cd-AgNPs, which further can be used as a novel biocidal agent against bacterial pathogens and a potent photo catalytic agent.